Epigenetically quantified immune cells in salivary glands of Sjögren's syndrome patients: a novel tool that detects robust correlations of T follicular helper cells with immunopathology. (19th July 2019) - Blokland, Sofie L M; van Vliet-Moret, Fréderique M; Hillen, Maarten R; Pandit, Aridaman; Goldschmeding, Roel; Kruize, Aike A; Bouma, Gerben; van Maurik, André; Olek, Sven; Hoffmueller, Ulrich; van Roon, Joel A G; Radstake, Timothy R D J
Abstract: Objective: To investigate whether epigenetic cell counting represents a novel method to quantify immune cells in salivary glands of patients with different forms of Sjögren's and sicca syndrome and to capture immunopathology and potentially aid in diagnosis. Methods: DNA from frozen salivary gland tissue sections of sicca patients was used for bisulphite conversion of demethylated DNA cytosine residues, followed by cell-specific quantitative PCR to calculate cell percentages in relation to total tissue cell numbers as quantified by housekeeping gene demethylation. The percentages of epigenetically quantified cells were correlated to RNA expression of matched salivary gland tissue and histological and clinical parameters. Results: The percentages of epigenetically quantified CD3, CD4, CD8, T follicular helper (Tfh) cells, FoxP3 + regulatory T cells and B cells were significantly increased in the salivary glands of patients with SS. Unsupervised clustering using these percentages identified patient subsets with an increased lymphocytic focus score and local B cell hyperactivity and classifies patients different from conventional classification criteria. In particular, Tfh cells were shown to strongly correlate with the expression of CXCL13, lymphocytic focus scores, local B cell hyperactivity and anti-SSA positivity. Conclusion: Epigenetic cell counting is a promising novel tool to objectively and easily quantify immune cells in the labial salivary gland of sicca patients, with a relatively small amount of tissue needed. In view of the potential of this technique to include a huge number of (cell-specific) biomarkers, this opens up new standardized ways of salivary gland analysis with high relevance for patient classification, understanding of immunopathology and monitoring of drug responses in clinical trials.